2020
DOI: 10.1007/s42832-020-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

A rice variety with a high straw biomass retained nitrogen and phosphorus without affecting soil bacterial species

Abstract: It is well documented that rice paddy fields act as agricultural wetlands that remove or retain nutrients; however, their associated effects on soil microbial communities are rarely reported. The present study evaluates the impact of rice variety on nutrient removal via plant uptake, nutrient retention in the soil, and bacterial associations in rice paddy fields, using a network analysis that compares the soil bacterial communities of two rice varieties. We found that the high-straw rice variety (YD-1) allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Acidobacteria Bryobacter, characterized as an aerobic chemo-organotrophic bacterium capable of utilizing various sugars, polysaccharides, and organic acids, plays a significant role in the C cycle 61 . In our forest edges, abundance of Bryobacter increased with soil OM content and concentrations of P with urbanization (Sup Table 2 & 4 ) suggesting Bryobacter is directly linked to P availability and soil OM content 62 . However, we observed no relationship between Bryobacter relative abundance (%) and P concentrations or organic matter across all of our forest soils (p > 0.10).…”
Section: Discussionmentioning
confidence: 74%
“…Acidobacteria Bryobacter, characterized as an aerobic chemo-organotrophic bacterium capable of utilizing various sugars, polysaccharides, and organic acids, plays a significant role in the C cycle 61 . In our forest edges, abundance of Bryobacter increased with soil OM content and concentrations of P with urbanization (Sup Table 2 & 4 ) suggesting Bryobacter is directly linked to P availability and soil OM content 62 . However, we observed no relationship between Bryobacter relative abundance (%) and P concentrations or organic matter across all of our forest soils (p > 0.10).…”
Section: Discussionmentioning
confidence: 74%
“…Other research has identified positive correlations between the abundance of Bryobacter and soil phosphorous availability (Liang et al., 2020; Malviya et al., 2021; Rosier et al., 2021). Bryobacter , along with other dominant soil genera in this study, likely contribute significantly to soil nutrient and carbon cycling processes.…”
Section: Resultsmentioning
confidence: 95%
“…The relative abundance of Bryobacter increased under GR24 treatment. Abundance of Bryobacter was positively correlated with soil health and directly correlated with available P concentration ( Huang et al, 2020 ; Liang et al, 2020 ). These results indicate suggest that SLs promote increase in abundance of beneficial bacteria and reduction of harmful bacteria in soil.…”
Section: Discussionmentioning
confidence: 99%